Faktor-Faktor yang Mempengaruhi Realisasi Penanaman Modal dalam Negeri di Provinsi Bali - Puspita Dewi, Komang Sri Ayu; Meydianawathi, Luh Gede (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2017)
This study aimed to determine the effect of simultaneous and partial number of tourist arrivals, the interest rate, the GDP and the regional autonomy policy towards domestic investment in the province of Bali. The data used in this research is secondary data. Data collected methods used in this study is on-participant observation method by collecting data from the Central Bureau of Statistics, Board of Investment and other relevant agencies. The analysis technique used in this research is multiple linear regression analysis, which is accompanied with the classical assumption. The result show that obtaining simultaneous variable number of tourist visits, the interest rate, GDP and regional autonomy significant effect on domestic investment in the province of Bali. Partially number of tourists visit mancanegra, the level of the GDP and the regional autonomy policy positive and significant impact on domestic realitation in Bali Province. Meanwhile, the partial interest rate a significant negative effect on domestic realitation in Bali Province.
Keywords: wisatawan mancanegara; suku bunga; PDRB; kebijakan otonomi daerah; PMDN